Preoperative oral immunonutrition in gastrointestinal surgical patients: How the tumour microenvironment can be modified. (August 2020) - D'Ignazio, Alessia; Kabata, Pawel; Ambrosio, Maria Raffaella; Polom, Karol; Marano, Luigi; Spagnoli, Luigi; Ongaro, Alessandra; Pieretti, Linda; Marrelli, Daniele; Biviano, Ivano; Roviello, Franco
Summary: Background & aims: This study is focused on the impact of enteral immunonutrition on the cell-mediated immune response in the microenvironment of gastric and colorectal cancers. Methods: This is a prospective pilot study approved by the local Ethics Committee. The immunophenotypic structure of the immune cells before (on the biopsy) and after (on the surgical sample) the administration of the immunonutrition in 16 patients is compared with 8 patients receiving regular diet. The samples of non-tumour tissue from sleeve-gastrectomy are used as non-neoplastic control. Antibodies were tested: CD4, CD8, PD-1, FOX-P3, CD68, CD163, CD80, CD21, CD56, PD-L1. We applied already well-known scoring systems for the evaluation of the immunohistochemistry and compared our data in the different groups by statistical analysis. Results: In treated patients, we detected a modulation of the immune response with higher number of cytotoxic and helper T-lymphocytes in the tumour microenvironment of the surgical specimens compared to the pre-operative biopsy, and a lower number of lymphocytes presenting an exhausted (i.e. double positive CD8 and PD-1 lymphocytes) and regulatory (i.e. double positive CD4 and FOX-P3 lymphocytes) phenotype. Moreover we observed the M1 polarization with a lower number of CD163 positive macrophages and the inhibition of the PD-1/PD-L1 pathway in treated patients. Conclusions: The immunonutrition impacts on the tumoral microenvironment of gastric and colorectal cancer activating the inflammatory pathway, in terms of humoral and cellular response.